# Recent questions tagged substitution

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the simultaneous equations $x+y=3$ and $2 x^{2}+4 x y-y=15$
Solve the simultaneous equations $x+y=3$ and $2 x^{2}+4 x y-y=15$Solve the simultaneous equations $x+y=3$ and $2 x^{2}+4 x y-y=15$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
What is the derivative of $\sinh (x)$ with respect to $x$ ?
What is the derivative of $\sinh (x)$ with respect to $x$ ?What is the derivative of $\sinh (x)$ with respect to $x$ ? ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the given system - or show that no solution exists: \begin{aligned} x+2 y &=& 1 \\ 3 x+2 y+& 4 z=& 7 \\ -2 x+y-& 2 z=&-1 \end{aligned}
Solve the given system - or show that no solution exists: \begin{aligned} x+2 y &=& 1 \\ 3 x+2 y+& 4 z=& 7 \\ -2 x+y-& 2 z=&-1 \end{aligned}Solve the given system - or show that no solution exists: \ \begin{aligned} x+2 y &amp;=&amp; 1 \\ 3 x+2 y+&amp; 4 z=&amp; 7 \\ -2 x+y-&amp; 2 z=&amp ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the equations for $x, y$, and $z$.
Solve the equations for $x, y$, and $z$.Solve the equations for $x, y$, and $z$. $x+0 y+3 z=2$ $2 x+3 y+2 z=1$ $2 x+2 y+3 z=3$ HINT: If $A=\left(\begin{array}{lll}2 &amp; 3 & ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 What is the most suitable substitution to use to solve the integral \int \frac{1}{\sqrt{t^{2}-81}} d t ? 0 answers 47 views What is the most suitable substitution to use to solve the integral \int \frac{1}{\sqrt{t^{2}-81}} d t ?What is the most suitable substitution to use to solve the integral \int \frac{1}{\sqrt{t^{2}-81}} d t ? &nbsp; A) t=9 \sec \theta. &nbsp; B) ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 The derivative with respect to x of \int_{\frac{\pi}{7}}^{x} e^{t^{2}} \operatorname{cosec}(t) d t is 0 answers 43 views The derivative with respect to x of \int_{\frac{\pi}{7}}^{x} e^{t^{2}} \operatorname{cosec}(t) d t isThe derivative with respect to x of \int_{\frac{\pi}{7}}^{x} e^{t^{2}} \operatorname{cosec}(t) d t is &nbsp; A) e^{x^{2}} \operatorname{cosec}( ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Evaluate \int_{1}^{2} \frac{1}{t+t^{2}} d t by completing the square and using trigonometric substitution. Show all your working. 0 answers 45 views Evaluate \int_{1}^{2} \frac{1}{t+t^{2}} d t by completing the square and using trigonometric substitution. Show all your working. Evaluate \int_{1}^{2} \frac{1}{t+t^{2}} d t by completing the square and using trigonometric substitution. Show all your working. ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Find \int \sin ^{2} \theta \cos ^{2} \theta d \theta . Show all your working. 0 answers 50 views Find \int \sin ^{2} \theta \cos ^{2} \theta d \theta . Show all your working.Find \int \sin ^{2} \theta \cos ^{2} \theta d \theta . Show all your working. ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Which of the following substitutions is most appropriate to evaluate  \int \frac{x^{4}}{\sqrt{x^{2}-1}} d x ?  0 answers 41 views Which of the following substitutions is most appropriate to evaluate  \int \frac{x^{4}}{\sqrt{x^{2}-1}} d x ? Which of the following substitutions is most appropriate to evaluate  \int \frac{x^{4}}{\sqrt{x^{2}-1}} d x ?  A. \quad x=\sqrt{u} B. \quad x ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Solve the equation \( 8^{2 x-5}=2^{x+1}$
Solve the equation $8^{2 x-5}=2^{x+1}$Solve the equation $8^{2 x-5}=2^{x+1}$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the system of equations below with Gauss-Jordan elimination. \begin{aligned} x+y-z &=10 \\ 2 x-y-z &=3 \\ -3 x-3 y+3 z &=-30 \end{aligned}
Solve the system of equations below with Gauss-Jordan elimination. \begin{aligned} x+y-z &=10 \\ 2 x-y-z &=3 \\ -3 x-3 y+3 z &=-30 \end{aligned}Solve the system of equations below with Gauss-Jordan elimination. \ \begin{aligned} x+y-z &amp;=10 \\ 2 x-y-z &amp;=3 \\ -3 x-3 y+3 z &amp;=-30 \end ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the system of equations below with GaussJordan elimination. \begin{aligned} x+\quad y+\quad z &=120 \\ 0.04 x+0.06 y+0.1 z &=6 \end{aligned}
Solve the system of equations below with GaussJordan elimination. \begin{aligned} x+\quad y+\quad z &=120 \\ 0.04 x+0.06 y+0.1 z &=6 \end{aligned}Solve the system of equations below with GaussJordan elimination. \ \begin{aligned} x+\quad y+\quad z &amp;=120 \\ 0.04 x+0.06 y+0.1 z &amp;=6 \end{a ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the system of equations below with GaussJordan elimination. \begin{aligned} x+\quad y &=10 \\ 0.08 x+0.12 y &=0.84 \end{aligned}
Solve the system of equations below with GaussJordan elimination. \begin{aligned} x+\quad y &=10 \\ 0.08 x+0.12 y &=0.84 \end{aligned}Solve the system of equations below with GaussJordan elimination. \ \begin{aligned} x+\quad y &amp;=10 \\ 0.08 x+0.12 y &amp;=0.84 \end{aligned} \ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the system of equations below with Gauss-Jordan elimination.
Solve the system of equations below with Gauss-Jordan elimination.Solve the system of equations below with Gauss-Jordan elimination. \ \begin{aligned} &amp;2 x+5 y=-6 \\ &amp;-3 x+y=-8 \end{aligned} \ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the system of equations by the Elimination Method. \begin{aligned} &0.5 x-0.25 y=-0.5 \\ &-2 x+3 y=10 \end{aligned}
Solve the system of equations by the Elimination Method. \begin{aligned} &0.5 x-0.25 y=-0.5 \\ &-2 x+3 y=10 \end{aligned}Solve the system of equations by the Elimination Method. \ \begin{aligned} &amp;0.5 x-0.25 y=-0.5 \\ &amp;-2 x+3 y=10 \end{aligned} \ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the system of equations by the Elimination Method. \begin{aligned} &0.1 x+0.3 y=1.4 \\ &9 x-3 y=-24 \end{aligned}
Solve the system of equations by the Elimination Method. \begin{aligned} &0.1 x+0.3 y=1.4 \\ &9 x-3 y=-24 \end{aligned}Solve the system of equations by the Elimination Method. \ \begin{aligned} &amp;0.1 x+0.3 y=1.4 \\ &amp;9 x-3 y=-24 \end{aligned} \ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the system of equations by the Elimination Method. \begin{aligned} &-2 x-5 y=18 \\ &10 x+2 y=2 \end{aligned}
Solve the system of equations by the Elimination Method. \begin{aligned} &-2 x-5 y=18 \\ &10 x+2 y=2 \end{aligned}Solve the system of equations by the Elimination Method. \ \begin{aligned} &amp;-2 x-5 y=18 \\ &amp;10 x+2 y=2 \end{aligned} \ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the system of equations by the Elimination Method. \begin{aligned} &2 x+3 y=-1 \\ &7 x-6 y=13 \end{aligned}
Solve the system of equations by the Elimination Method. \begin{aligned} &2 x+3 y=-1 \\ &7 x-6 y=13 \end{aligned}Solve the system of equations by the Elimination Method. \ \begin{aligned} &amp;2 x+3 y=-1 \\ &amp;7 x-6 y=13 \end{aligned} \ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the system of equations by the Substitution Method. \begin{aligned} &2 x-3 y=4 \\ &5 x+2 y=29 \end{aligned}
Solve the system of equations by the Substitution Method. \begin{aligned} &2 x-3 y=4 \\ &5 x+2 y=29 \end{aligned}Solve the system of equations by the Substitution Method. \ \begin{aligned} &amp;2 x-3 y=4 \\ &amp;5 x+2 y=29 \end{aligned} \ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve $x^{2} \pm 2 x=4$
Solve $x^{2} \pm 2 x=4$Solve $x^{2} \pm 2 x=4$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve for $x$ in $5 x+3=28$
Solve for $x$ in $5 x+3=28$Solve for $x$ in $5 x+3=28$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Divide $x^{3}-3 x^{2}+3 x-1$ by $x-1$
Divide $x^{3}-3 x^{2}+3 x-1$ by $x-1$Divide $x^{3}-3 x^{2}+3 x-1$ by $x-1$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
$5(z+1)=3(z+2)+11$ Solve for $z$
$5(z+1)=3(z+2)+11$ Solve for $z$$5(z+1)=3(z+2)+11$ Solve for $z$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the simultaneous equations: $\frac{2}{\sqrt{x}}+\frac{3}{\sqrt{y}}=2$ and $\frac{4}{\sqrt{x}}-\frac{9}{\sqrt{y}}=-1$
Solve the simultaneous equations: $\frac{2}{\sqrt{x}}+\frac{3}{\sqrt{y}}=2$ and $\frac{4}{\sqrt{x}}-\frac{9}{\sqrt{y}}=-1$Solve the simultaneous equations: $\frac{2}{\sqrt{x}}+\frac{3}{\sqrt{y}}=2$ and $\frac{4}{\sqrt{x}}-\frac{9}{\sqrt{y}}=-1$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the simultaneous equations $a+b=4$ and $2 a+b=6$
Solve the simultaneous equations $a+b=4$ and $2 a+b=6$Solve the simultaneous equations $a+b=4$ and $2 a+b=6$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the simultaneous equation $4.9 x+1.5 y=38.3$ and $2.7 x-8.6 y=17.8$
Solve the simultaneous equation $4.9 x+1.5 y=38.3$ and $2.7 x-8.6 y=17.8$Solve the simultaneous equation $4.9 x+1.5 y=38.3$ and $2.7 x-8.6 y=17.8$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the simultaneous equations $3x+y=8$ and $x+2 y=6$
Solve the simultaneous equations $3x+y=8$ and $x+2 y=6$Solve the simultaneous equations $3x+y=8$ and $x+2 y=6$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve the simultaneous equations: $3 x-y+z=5$; $2 x+2 y+3 z=4$ and $x+3 y-z=11$
Solve the simultaneous equations: $3 x-y+z=5$; $2 x+2 y+3 z=4$ and $x+3 y-z=11$Solve the simultaneous equations: $3 x-y+z=5$; $2 x+2 y+3 z=4$ &nbsp;and $x+3 y-z=11$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Given the following simultaneous equations: $x+3 y=-1$ and $-3 x+6 y=8$, solve the given simultaneous equations by the substitution method.
Given the following simultaneous equations: $x+3 y=-1$ and $-3 x+6 y=8$, solve the given simultaneous equations by the substitution method.Given the following simultaneous equations: $x+3 y=-1$ and $-3 x+6 y=8$, solve the given simultaneous equations by the substitution method. ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve simultaneous equations $y-3 x=5$ and $2 y+3 x=28$ by the method of elimination and substitution.
Solve simultaneous equations $y-3 x=5$ and $2 y+3 x=28$ by the method of elimination and substitution.Solve simultaneous equations $y-3 x=5$ and $2 y+3 x=28$ by the method of elimination and substitution. ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
What is the value of 5t^2-7 when t=4?
What is the value of 5t^2-7 when t=4?What is the value of $5t^2-7$ when $t=4$? ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
If r = 9, b = 5, and g= −6, what does (r + b − g)(b + g) equal?
If r = 9, b = 5, and g= −6, what does (r + b − g)(b + g) equal? If&nbsp;r&nbsp;= 9,&nbsp;b&nbsp;= 5, and&nbsp;g= −6, what does (r&nbsp;+&nbsp;b&nbsp;−&nbsp;g)(b&nbsp;+&nbsp;g)&nbsp;equal? ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
If a = - 2 and b = 3 then a^2 – b^3 is equal to:
If a = - 2 and b = 3 then a^2 – b^3 is equal to:If a = - 2 and b = 3 then a^2 – b^3 is equal to: ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
How do I solve the simultaneous equation $5u+3v=-17 ; 2u+v=-7$
How do I solve the simultaneous equation $5u+3v=-17 ; 2u+v=-7$How do I solve the simultaneous equation $5u+3v=-17 ; 2u+v=-7$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Calculate the value of $c^3 + 12$ if $c = 3$
Calculate the value of $c^3 + 12$ if $c = 3$Calculate the value of $c^3 + 12$ if $c = 3$ ...
What is the value of $3 − \frac{k}{2}$ if $k = 4$?
What is the value of $3 − \frac{k}{2}$ if $k = 4$?What is the value of $3 − &nbsp;\frac{k}{2}$ &nbsp;if $k = 4$? ...